2018
DOI: 10.1111/epi.14522
|View full text |Cite
|
Sign up to set email alerts
|

Perampanel in routine clinical use in idiopathic generalized epilepsy: The 12‐month GENERAL study

Abstract: Summary Objective To analyze the effectiveness and tolerability of perampanel across different seizure types in routine clinical care of patients with idiopathic generalized epilepsy (IGE). Methods This multicenter, retrospective, 1‐year observational study collected data from patient records at 21 specialist epilepsy units in Spain. All patients who were aged ≥12 years, prescribed perampanel before December 2016, and had a confirmed diagnosis of IGE were included. Results The population comprised 149 patients… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

26
112
3
2

Year Published

2019
2019
2023
2023

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 94 publications
(153 citation statements)
references
References 46 publications
26
112
3
2
Order By: Relevance
“…Other real-world studies such as the one by Villanueva and colleagues [15] have reported similar results while also looking at different seizure types in GGE. Juvenile myoclonic epilepsy (JME) was the most common syndrome in their subjects at 40%, compared with 76% in the current cohort.…”
Section: Discussionsupporting
confidence: 59%
“…Other real-world studies such as the one by Villanueva and colleagues [15] have reported similar results while also looking at different seizure types in GGE. Juvenile myoclonic epilepsy (JME) was the most common syndrome in their subjects at 40%, compared with 76% in the current cohort.…”
Section: Discussionsupporting
confidence: 59%
“…On the other hand, an AMPA antagonist, perampanel, has been approved as an anti-seizure drug for focal seizures and primary generalized tonic-clonic seizures [25][26][27][28][29]. Recent preliminary observations have suggested that perampanel may be efficacious in patients with other seizure types such as myoclonic or absence seizures [30,31]. As noted above, agonists of both NMDA and AMPA receptors have been shown to elicit seizures in animal models, but clinical study results differ between the two receptor types.…”
Section: Introductionmentioning
confidence: 99%
“…Case reports indicate that adult patients demonstrate gradual decline in cognitive abilities (21). Perampanel (PMP), an AMPA receptor (AMPAR) antagonist recently approved by the Food and Drug Administration, has shown significant promise for multiple seizure types in idiopathic generalized epilepsies, including absence seizures (22). Its use in infants with epilepsy is in clinical trial (23).…”
mentioning
confidence: 99%